2019
DOI: 10.1186/s12913-019-4739-0
|View full text |Cite
|
Sign up to set email alerts
|

The importance of herbal medicine use in the German health-care system: prevalence, usage pattern, and influencing factors

Abstract: BackgroundPrevalence rates for herbal medicine (HM) have been increasing worldwide. However, little is known about prevalence, user characteristics, usage pattern and factors influencing HM usage for the general German population.MethodsA nationwide online survey on HM usage was conducted in Germany. The 2906 participants were categorised into three groups: the ones who used HM in the last 12 months, the ones who did not use HM in the last 12 months but in their lifetime, and the ones who did not use HM until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 40 publications
(56 reference statements)
6
61
2
Order By: Relevance
“…Another facilitator expressed in this study is patient’s belief regarding herbal medicine which is consistent with a number of studies [ 4 , 13 , 21 , 28 , 46 ]. The nurses uttered that a patient with a positive belief about herbal medicine will surely take the medication [ 4 , 21 , 28 , 46 ]. The previous studies further buttressing the assertion by nurses posited positive beliefs such as the natural nature and beneficial role of CAM as reasons for CAM use [ 4 , 21 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Another facilitator expressed in this study is patient’s belief regarding herbal medicine which is consistent with a number of studies [ 4 , 13 , 21 , 28 , 46 ]. The nurses uttered that a patient with a positive belief about herbal medicine will surely take the medication [ 4 , 21 , 28 , 46 ]. The previous studies further buttressing the assertion by nurses posited positive beliefs such as the natural nature and beneficial role of CAM as reasons for CAM use [ 4 , 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…The nurses uttered that a patient with a positive belief about herbal medicine will surely take the medication [ 4 , 21 , 28 , 46 ]. The previous studies further buttressing the assertion by nurses posited positive beliefs such as the natural nature and beneficial role of CAM as reasons for CAM use [ 4 , 21 ]. At the Brim South District in the Eastern Region of Ghana, some midwives who had positive belief in the effectiveness of CAM recommended its use among pregnant women attending their facilities [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients from Asian cultural backgrounds expressed more negative views about medication than those from European cultural backgrounds. The exception for European backgrounds was that the use of herbal remedies was found to be very high in the general German population [ 35 ]. Patients from Asian cultural backgrounds were significantly more likely to perceive medicines as being intrinsically harmful, addictive substances and that the unnatural origins of medicines was dangerous and that complementary treatments are more ‘natural’ and therefore safer [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the existing literature, it is reported that people, including PwMS who use DIHES, often receive their information on DIHES from sources such as family, friends, books, magazines, or the internet [ 6 , 36 38 ]. The present study finds that from the participants’ perspective, knowledge regarding DIHES did not have to be scientifically based to be perceived as valid and useful.…”
Section: Discussionmentioning
confidence: 99%